IMPLEMENTASI PENGAMALAN PANCASILA DI PONPES DINIYYAH PASIA UNTUK MENANGKAL BERKEMBANGNYA PAHAM RADIKALISME DI KABUPATEN AGAM - Pratama, Robbyanandri; Darmoko, Darmoko (JURNAL DWIJA KUSUMA, 2025)
Radicalism remains an ideological threat in Indonesia and has the potential to infiltrate religious educational institutions, including pesantren. Several findings indicate that a small number of pesantren have been associated with exclusive and intolerant teachings. This study aims to examine the implementation of Pancasila values at Pondok Pesantren Diniyyah Pasia and its role in preventing the spread of radicalism in Agam Regency. This research employs a library research approach. The findings show that Pesantren Diniyyah Pasia practices Pancasila through the strengthening of faith and morality, the promotion of tolerance, multicultural student life, decision-making through deliberation, and social and economic engagement. These practices reinforce students’ nationalism and serve as a barrier against radicalism. Although the pesantren demonstrates strong commitment to moderation and national values, continued oversight of educational processes is necessary to prevent the infiltration of intolerant ideologies. Thus, Pesantren Diniyyah Pasia holds strategic potential as a model for strengthening Pancasila and preventing radicalism at the local level.